My Journey of Learning - Chunawala, Aafreen; Jain, Pratik (Homœopathic Links, 2017)
This personal piece comes from a young Indian homeopath who has documented her transformative learning journey at Dr. Rajan Sankaran's ‘the other song’ Academy (TOS) in Mumbai. Throughout the article, she narrates and highlights some key learning points, along with concise and illustrative cases. She examines various concepts including the artistic use of the repertory, the use of an anchor in case-taking, structured repertorisation, miasm, keynote symptoms, using rare remedies, finger printing, Reference Works, sensation, symptom syndrome, levels of experience, psycho-neuro-endocrine-immunological axis, kingdom, potency and follow-up.
Keywords: Synergy; Nux moschata; Magnesium carbonicum; Sepia succus; Lycopodium clavatum; Lyssinum; Petroleum; Cicuta virosa; Aethusa cynapium; Tarentula; Brachypelma smithi pili; Oleander; Morgan gaertner; Lac asinum; Calcarea carbonica; Carica papaya; Oncorhynchus tshawytscha; Cocculus Indicus; Tanacetum; DPT; Borax; Ranunculus Bulbosus; Graphites; Streptococcin; Ferrum phosphoricum; Antimonium crudum; Sulphur; Kali carbonicum; Ocimum sanctum; Azadirachta indica; Aristolochia clematitis